Where Does Multinational Investment Go with Territorial Taxation? : Evidence from the UK - Liu, Li (IMF Working Papers; Working Paper ;, 2018)
In 2009, the United Kingdom changed from a worldwide to a territorial tax system, abolishing dividend taxes on foreign repatriation from many low-tax countries. This paper assesses the causal effect of territorial taxation on real investments, using a unique dataset for multinational affiliates in 27 European countries and employing the difference-in-difference approach. It finds that the territorial reform has increased the investment rate of UK multinationals by 15.7 percentage points in low-tax countries. In the absence of any significant investment reduction elsewhere, the findings represent a likely increase in total outbound investment by UK multinationals.